2019
DOI: 10.1021/acs.jmedchem.8b01808
|View full text |Cite
|
Sign up to set email alerts
|

Applications of Deuterium in Medicinal Chemistry

Abstract: The use of deuteration in medicinal chemistry has exploded in the past years, and the FDA has recently approved the first deuterium-labeled drug. Precision deuteration goes beyond the pure and simple amelioration of the pharmacokinetic parameters of a drug and might provide an opportunity when facing problems in terms of metabolism-mediated toxicity, drug interactions, and low bioactivation. The use of deuterium is even broader, offering the opportunity to lower the degree of epimerization, reduce the dose of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
416
0
9

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 585 publications
(427 citation statements)
references
References 122 publications
2
416
0
9
Order By: Relevance
“…[14] N-Methyl groups have the propensity to undergo metabolic oxidation, and the replacement of a-hydrogen atoms with deuterium has recently gained traction as am eans of reducing metabolic liabilities of redox-active groups. [15] The installation of at rideuteriomethyl group is not straightforward and typically requires several steps. [15] Given the widespread availability of acetic acid-d 4 as as olvent for NMR spectroscopy,w ee xplored the reaction of acetic acid-d 4 with aromatic amines as as imple,y et hitherto unavailable,o nestep method of N-trideuteriomethylation (Scheme 4).…”
Section: Angewandte Chemiementioning
confidence: 99%
See 1 more Smart Citation
“…[14] N-Methyl groups have the propensity to undergo metabolic oxidation, and the replacement of a-hydrogen atoms with deuterium has recently gained traction as am eans of reducing metabolic liabilities of redox-active groups. [15] The installation of at rideuteriomethyl group is not straightforward and typically requires several steps. [15] Given the widespread availability of acetic acid-d 4 as as olvent for NMR spectroscopy,w ee xplored the reaction of acetic acid-d 4 with aromatic amines as as imple,y et hitherto unavailable,o nestep method of N-trideuteriomethylation (Scheme 4).…”
Section: Angewandte Chemiementioning
confidence: 99%
“…[15] The installation of at rideuteriomethyl group is not straightforward and typically requires several steps. [15] Given the widespread availability of acetic acid-d 4 as as olvent for NMR spectroscopy,w ee xplored the reaction of acetic acid-d 4 with aromatic amines as as imple,y et hitherto unavailable,o nestep method of N-trideuteriomethylation (Scheme 4). Gratifyingly,acetic acid-d 4 mediated the desired N-trideuteriomethylation, and av ariety of N-CD 3 -substituted anilines 85-98 were accessed from the corresponding aniline precursors,thus establishing astraightforward N-trideuteriomethylation route directly from ar eadily available deuterated solvent.…”
Section: Angewandte Chemiementioning
confidence: 99%
“…[2,3] In drug discovery,r adioactive tritiumt racers are increasingly utilized as discoveryt ools, [4] in covalent binding assays, [5] for tissue distribution studies, [6] for in vivo profiling of new drug candidates and for other life science applications. [3,7,8] Based on homogeneouso rh eterogeneous catalysis, numerousH IE methods have already been described. [1, 2, 4c, 9] Besides ongoing active research for C(sp 3 )ÀHa ctivation/deuteration, [10] particulara ttention has been paid to the selective ortho-directed HIE of aromatic substratesw ith commercial Crabtree's [11] and Kerr's catalyst.…”
mentioning
confidence: 99%
“…The corresponding crystal structure was obtained (see the Supporting Information, Section 10.4). Selectively deuterated substrates are of interest for medicinal chemistry studies, in which the use of deuteration has shown, in some cases, to improve the pharmacokinetic properties . Furthermore, fluorinated cubane ethers ( 14 and 15 ) were obtained in moderate to good yields from TFE (2,2,2‐trifluoroethanol) and HFIP (1,1,1,3,3,3‐hexafluoroisopropanol), respectively.…”
Section: Methodsmentioning
confidence: 99%
“…Selectively deuterated substrates are of interest for medicinal chemistry studies, in which the use of deuteration has shown, in some cases, to improve the pharmacokinetic properties. [34] Furthermore, fluorinated cubane ethers (14 and 15) were obtained in moderate to good yields from TFE (2,2,2-trifluoroethanol) and HFIP (1,1,1,3,3,3-hexafluoroisopropanol), respectively. The application of fluorinated alcohols was not viable using the C/PVDF anode, which swells in fluorinated solvents (see the Supporting Information, Section 3.5.3), but was possible using a Pt anode.…”
mentioning
confidence: 99%